The hazard of old lead mines in Wales. Issue 4 (December 1977) - Thomas, H F; Moore, F; Welsby, E; Elwood, P C; Firth, J N
Abstract : Two population surveys were conducted near old lead workings in Wales. The first, at Y Fan in the middle of Wales, gave evidence suggestive of a gradient in blood lead level, highest in subjects resident close to the contaminated spoil heaps, and lowest in those who lived in farms some distance away. However, the gradient was significant (P less than 0.05) only in males, and all but one of the blood lead levels were below 2.0 mumol/l. In the second survey, at Halkyn in North Wales, levels in subjects living in the area contaminated by spoil were compared with those in subjects living in a nearby industrial area, and with subjects in a market town some distance away. Mean blood lead in people living in the three areas were homogeneous. These studies give no evidence that old lead workings in Wales are a serious hazard to health.